أقوال السلف لخير الخلف: الامام محمد بن علي الباقر عليه السلام - موسي، ميثم خلف (جامعة القادسية - كلية الآداب, 2018)
حظيت حياة الأمام محمد بن علي الباقر (عليه السلام) باهتمام كثير من الباحثين سواء من السنة والشيعة، حيث كان لحياة الإمام الهمام الأثر الكبير على الفريقين، لا لأنه من أهل بيت الرسول محمد (صلى الله عليه وآله وسلم) فحسب، إنما كان عليه السلام غزير العلم ورعا تقينا تلتجئ إلية الناس من كل الطوائف والنحل، فكان لزاما على الباحثين إعطاء أهمية كبيرة في أبحاثهم من أجل عرض حياة هذا الإمام التقي الورع في هذا المجال. يرمي البحث إلى تسليط الضوء على جانبا من كلمات علماء، وأعلام أهل السنة، وهي تشيد بمقام الإمام الباقر (عليه السلام)، وتبين جلالة قدره وعظم منزلته عند باقي طوائف المسلمين.
The life of Imam Muhammad bin Ali al-Baqir (peace be upon him) has attracted the interest of many scholars, both Sunnis and Shiites, where the Imam's life had a great impact on the two groups, not only because of the family of the Prophet Muhammad (peace and blessings of Allaah be upon him) It was necessary for scholars to give great importance to their research in order to present the life of this pious imam in this field. The research aims at shedding light on some of the words of the scholars and the flags of the Sunnis. It praises the imam of al-Baqir (peace be upon him) and shows his majesty and greatness in the rest of the Muslim communities.
Keywords: أبو جعفر، محمد بن علي الباقر، ت. 114 هـ. -- التراث الدينى -- التاريخ الاسلامى